(untitled) (BioMedical Research in Medicine (BMR Medicine) (ISSN 2349-0756), 2024)
The present study is carried out in Sangli, Maharastra in India who visited hospital either as a patient or accompanied the patients. The consent of the Parents and the individual was obtained after explaining them the objectives of the study. X ray were obtained he method of classification was categorizes in 5 stages based on the standard protocol prescribed. The union of head of Humerus with the shaft occurs between 18 to 19.5 years. The fusion of lower end of Ulna with shaft is complete by 18 to 19 years. The fusion of lower end of Radius has occurred 19 to 19.5 years. Where as lower end of Ulna 0.5 year earlier than the lower end of Radius in same individuals. Complete union of epiphysis of acromion of scapula occurs by 18 to 18.5 Years.